KESIAPAN SUMBER DAYA MANUSIA DALAM IMPLEMENTASI PEMANFAATAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) UNTUK MENINGKATKAN EFISIENSI PELAYANAN RAWAT JALAN - Ni Wayan Eka Arimas; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to assess the level of human resource (HR) readiness in the use of SIMRS and its implications for the efficiency of outpatient services. The research method used is a literature study by reviewing various scientific articles, books, and recent research reports relevant to the topic. The results of the review indicate that HR readiness can be categorized into three levels: low, medium, and high, with different characteristics and impacts on service quality. Hospitals with high HR readiness are characterized by adequate digital competency, managerial support, and an adaptive organizational culture, thereby reducing patient waiting times, increasing data accuracy, strengthening inter-unit coordination, and encouraging patient satisfaction. Conversely, low readiness results in slow administrative processes, a high risk of input errors, and increased resistance to change. The main obstacles identified include limited digital literacy, HR resistance, excessive workload, and minimal technical support. Recommended strategies include ongoing training, technical assistance, organizational change management, workload adjustments, and regular evaluation to ensure sustainable implementation.